O teatro anarquista como prática social do movimento libertário (São Paulo e Rio de Janeiro de 1901 a 1922) - Hipólide, Eduardo Gramani (2012)
This master dissertation is about the Anarchist Theater in Rio de Janeiro and São Paulo, between 1901 and 1922. The main objective to conduct this study is to analyze theater as a social practice of the libertarian movement occurred in those important Brazilian cities. The clip shown here chronologically covers the period when libertarian segments of the working class directly influenced the labor movement. In an attempt to reconstruct the trajectories of different amateur groups who played in worker s parties, we seek in this research to find out about some of the subjects involved in those dramatic activities. Sure that the anarchist theater established dialogues with numerous libertarian segments in the working class, we analyze the relationships between the activities of amateur theater groups with other social practices of the anarchist labor movement trend, or socialist revolutionary, who also constituted the movement in that period. The focus of the approach to the plays that were staged in the worker s parties was not confined to mere structural analysis of that. Our focus was to face the political meaning of such plays and the possible resonance of the specific content of these texts on the pages of the Press Working. In addition to the theater texts, we also investigate the fragmentary evidences of what the Press working brought about the theater practices and about the ideas-images conveyed by the works that comprise the corpus of this research. Our continuous effort was not to lose sight of the focus in this research that is the analysis of Anarchist Theater as constituent part of the complex labor movement in the early 20th Century. From this perspective, the activities around that theater acquired a dynamic and active character. Thus, both, scenarios and plays were discussed here as direct interventions within the organized movement of the working class